VALIDATING THE MEASURES AND ASSESSING THE DIMENSIONS OF PURCHASE BEHAVIOR IN APARTMENT SCENARIO IN INDIAN PERSPECTIVE - Sharma, Devyani; Singh, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
As the data and technology-based interference in real estate decision making is increasing, the customer work behavior and builder technology usage is seemingly shaping value propositions in more than one way. While recent research has begun to take technology imprint as seriously yet very few studies have sought to validate the measures and assess the dimensions of purchase behavior in apartment scenario in Indian perspective. This research begins to address the instrument’s construct validity by arriving at a single instrument with confirmatory factor analysis and proposes broad dimensions that fit the set of data effectively. Results have practical implications for real estate marketers but also conceptual implications pertaining to application of these benchmarks in industrial perspective.